1994
DOI: 10.21273/jashs.119.3.524
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Cherimoya (Annona cherimola Mill.) to Cold Storage

Abstract: Fino de Jete' cherimoya fruit were stored at 20, 10, 8, or 6C, 80% relative humidity. Two rises of CO 2 production and an ethylene rise following the first peak of respiration were obtained in fruit held at 20C. The ripe stage coincided with the onset of the second respiratory rise. Soluble sugar and organic acid concentration were maximal, and flesh firmness was 18 N in ripe fruit. Lower temperature reduced respiration rate and ethylene production; however, some stimulation of ethylene synthesis was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 10 publications
3
14
0
1
Order By: Relevance
“…It has been reported that fruits that suffer chilling-injury symptoms such as cucumber, 17 melon, 26 cherimoya, 27 and avocado 28 increase ethylene production under chilling conditions; however, other fruits, such as peaches and nectarines, have been found to inhibit ethylene production at low temperatures, 29,30 similar to what we found in oil palm fruits. Some authors report that temperatures between 5 and 10 • C weakened fruit tissues due to the effects of different metabolic processes in response to chilling stress.…”
Section: Changes In Ethylene Production and Respiration During The Cosupporting
confidence: 87%
“…It has been reported that fruits that suffer chilling-injury symptoms such as cucumber, 17 melon, 26 cherimoya, 27 and avocado 28 increase ethylene production under chilling conditions; however, other fruits, such as peaches and nectarines, have been found to inhibit ethylene production at low temperatures, 29,30 similar to what we found in oil palm fruits. Some authors report that temperatures between 5 and 10 • C weakened fruit tissues due to the effects of different metabolic processes in response to chilling stress.…”
Section: Changes In Ethylene Production and Respiration During The Cosupporting
confidence: 87%
“…However, at the end of the storage period (23 days) there was an increase in PEPC activity, which would seem to indicate that the protective effect of the CO 2 was progressively lost when storage was prolonged. Despite this possible loss of the protective effect of CO 2 , at the end of storage the level of citrate, a compound that we previously reported as a marker of chilling damage in cherimoya fruit (5), was significantly higher in nontreated than in CO 2 -treated fruit (Figure 2). …”
Section: Discussionmentioning
confidence: 70%
“…Controlled atmospheres, with high CO 2 and low O 2 concentrations, have been shown to control some physiological disorders, thereby extending the storage period of fruit and vegetables (3). Cherimoya fruit is a chilling-sensitive fruit in which the occurrence of chilling injury (CI) is readily assessed by changes in pH evolution and accumulation of citrate constitute (4,5). Reports on the application of controlled atmospheres with high CO 2 levels suggest that these help prevent CI in cherimoya fruit by modulating the phenolic response associated with cell adhesion and hardening (6), maintaining flesh firmness and chlorophyll content, and maintaining levels of ribulose 1,5-biphosphate carboxylase and polygalacturonaserelated proteins (7).…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers use penetration tests to evaluate cherimoya softening (Alique, Zamorano, Calvo, Carmen, & De La Plaza, 1994;Brown et al, 1988;Martinez, Serrano, Pretel, Requelme, & Romojas, 1993;Sanchez, Zamorano, Hernandez, & Alique, 1998). However, since the edible part of cherimoya fruit is characterized by soft segments arranged around its longitudinal axis and the presence of many hard seeds, localized measurements such as those achieved by the penetration test may be highly biased by the orientation of the segments or the presence of nearby seeds (Peleg, 1979).…”
Section: Firmnessmentioning
confidence: 99%